Pengaruh Kualitas Produk, Citra Merek Dan Lokasi Terhadap Kepuasan Konsumen Warung Kopi Prada Di Surabaya - Erwin Tri Kurniyanto; Sugiharto Sugiharto; Achmad Daengs GS; Rina Dewi; Harsono Teguh (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
The coffee shop industry is one of the industries with the fastest development and demand. Every year the development and growth of the number of coffee shops opened in Indonesia is always increasing. By providing a product that is different from other coffee shops through the characteristics that coffee is served to customers, it can make the coffee shop always visited by customers, besides that, a brand image that is easy to remember and a strategic location will be able to attract customers to come to enjoy the coffee. The reason of this think about was to decide the impact of Product, Location, and Brand Image on Warkop Prada's Shopper Fulfillment variable in Surabaya. This inquire about was conducted employing a quantitative approach. The research information is within the frame of a test of 96 respondents in which the test is taken using Lemeshow. The information collection strategy may be a survey. Information investigation utilized in this think about was numerous direct relapse investigation with SPSS 26 computer program. The information that met the legitimacy test, unwavering quality test, and classic presumption test were handled to deliver a relapse condition: Y = 18.397 + 0.168X1 + 0.194X2 + 0.549X3 + e. The comes about of the investigation carried out can be seen through the comes about of the t test it can be seen that the factors Product (X1), Brand Image (X2), and Location (X3) have a fractional impact on the Customer Satisfaction (Y) Warkop Prada in Surabaya with each having t number (2.167), t check (2.288) and t number (2.638) which is more noteworthy than t table (1.66088). The comes about of the F test in this study appear that the calculated F esteem (5.475) is more noteworthy than F table (3.09), which implies that the autonomous factors are Product (X1), Brand Image (X2), and Location (X3) factors at the same time influence the variable Customer Satisfaction (Y) Warkop Prada in Surabaya